Integrating physiology into the first two years of a new osteopathic medical school curriculum - Slater, Natalie F.; Nizamutdinova, Irina; Jacobs, Blaine A.; Slater, Robert T.; Bradley, Jessica M. (Frontiers in Physiology, 2023)
The integrated curriculum is a hot topic in curriculum reform in undergraduate medical education; however, there are varying definitions of the term, and resources guiding the integration of specific disciplines throughout the first 2 years of undergraduate medical education in a learner-centered curriculum are limited. Our first class matriculated into our osteopathic medical school in 2017, and since then we have developed and implemented a learner-centered, integrated curriculum that begins on day one for our learners. This paper will discuss our experience with the development and implementation of the University of the Incarnate Word School of Osteopathic Medicine (UIWSOM) curriculum with specific emphasis on how we incorporate physiology into it.